Human gait recognition and classification using similarity index for various conditions - Makhdoomi, Nahid A.; Gunawan, Teddy Surya; Habaebi, Mohamed Hadi (2013)
Gait recognition is usually referred to signify the human identification by the style/way people walk in image sequences. Our aim is to implement the traditional gait recognition algorithm and to show the variation in gait recognition when subject is observed parallel to camera under three conditions- walking normal, carrying a bag and wearing a coat. However in this case, the work devises a novel method for the purpose of similarity computation rather than the traditional recognition where the overall recognition rate of 78.57 percent was obtained.